A scoping review of prehabilitation interventions for arthroplasty patients - Prithi Pillay-Jayaraman; Verusia Chetty; Stacy Maddocks (South African Journal of Physiotherapy, 2023)
Background: Osteoarthritis (OA) is a long-term condition that causes significant impairment, and because of the increasing prevalence of OA, the demand for arthroplasty will continue to rise. However, the demand will not be matched by availability, because of prioritisation of trauma-related surgeries. Implementing prehabilitation could assist physiotherapists in having an impact on improving access by reducing the length of stay.